Planning for Cultural Ecosystem Services: A Study of Socialist and Post-Socialist Zagreb, Croatia - Tandarić, Neven (2022)
Ever since the early 2000s, there has been considerable research on the contribution of cultural ecosystem services (CES) to human wellbeing. However, their application in planning has lagged because they differ profoundly from other kinds of ecosystem services. Moreover, most studies on practical aspects of CES have been carried out in high-income countries. In contrast, socialist and post-socialist perspectives have rarely been addressed despite studies indicating that socialist regimes used to provide abundant urban green and blue spaces (UGBS), which are considered the main providers of CES in urban areas. This thesis addressed this gap by exploring how urban planning in Zagreb, Croatia, incorporated, enabled and responded to CES across different socio-political and ideological periods, i.e. socialist (1945-1991) and post-socialist (after 1991) regimes. The study involved the collection and analysis of spatial data (historical aerial images), planning documents (historical urban plans), and interviews with 88 participants (park users, gardeners, urban planners, academics, and local activists). To facilitate analysis, a new framework for researching planning considerations of CES was devised, named the “hatch and grow” strategy. Four case study units were selected based on the time of construction and the presence of specific types of UGBS: (1) the Lower Town, (2) Trnsko and Siget neighbourhoods, (3) Savica Neighbourhood, and (4) Jarun and Vrbani neighbourhoods. The spatial analysis of aerial images and urban plans of Zagreb confirmed the hypothesis that the provision of UGBS peaked in the socialist period and virtually died out in the post-socialist period. Subsequent content analyses of urban plans and interview transcripts confirmed the more beneficial role of the utilitarian socialist approach to urban nature for human–nature interactions compared to the capital-oriented post-socialist urban planning. While interviewed park users indicated a number of CES generated in socialist parks, gardeners suggested that the provided opportunities were not as diverse to satisfy all residents who thus created wild collective gardens to elicit different sets of CES. The proposed framework for researching planning consideration of CES helped explain links between UGBS, users and CES from a historical perspective. This research demonstrated the complex yet profound legacy of historical socio-political context on contemporary urban CES, and the important implications this has for planning for urban CES.